2004
DOI: 10.1177/1534735403261831
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetables: Cancer Protective Mechanisms of Glucosinolate Hydrolysis Products and Selenium

Abstract: Dietetic professionals urge Americans to increase fruit and vegetable intakes. The American Institute of Cancer Research estimates that if the only dietary change made was to increase the daily intake of fruits and vegetables to 5 servings per day, cancer rates could decline by as much as 20%. Among the reasons cited for this health benefit are that fruits and vegetables are excellent sources of fiber, vitamins, and minerals. They also contain nonnutritive components that may provide substantial health benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
199
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(210 citation statements)
references
References 63 publications
3
199
0
8
Order By: Relevance
“…Indole-3-carbinol is extracted from cruciferous vegetables by hydrolysis of glucosinolates (6). Many previous in vitro studies have shown that I3C causes significant growth inhibition of a variety of tumor cell lines by inducing cell cycle arrest and apoptosis (8,10,12,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole-3-carbinol is extracted from cruciferous vegetables by hydrolysis of glucosinolates (6). Many previous in vitro studies have shown that I3C causes significant growth inhibition of a variety of tumor cell lines by inducing cell cycle arrest and apoptosis (8,10,12,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, epidemiological studies suggest that the intake of broccoli, cauliflower and other cruciferous vegetables can significantly reduce the incidence of cancers of the bladder, pancreas, colon, lung and stomach (2)(3)(4)(5). Indole-3-carbinol (I3C) has recently been identified as an important tumoricidal component found in cruciferous vegetables and particularly in members of the genus Brassica (6,7). A number of studies have shown that I3C induces cell cycle arrest in the G1 phase in cancer cells (8,9), promotes apoptosis (8)(9)(10) and prevents tumor invasion and metastasis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Tests on animals and in vitro tests drew attention to the degradation products of glucosinolates which suppress the division of cancer cells, and accelerate the controlled death of the cell with damaged DNA. Furthermore, the protective effect of the enzyme degradation products of glucosinolates is associated with the induction of detoxifying enzymes in the tissues of the gastrointestinal tract, particularly of glutathione transferase, levelling the active form of carcinogenic compounds [21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…They have recently attracted considerable attention because of a wide range of bioactivities, including functioning as antimicrobial compounds (1,2), deterrents of generalist herbivores (3), herbicides (4), and anticarcinogenic agents (5). Sulforaphane, a metabolite of methionine-derived 4-methylsulfinylbutyl glucosinolate (glucoraphanin), has received special attention because of its potent anticarcinogenic activity (6,7).…”
Section: Introductionmentioning
confidence: 99%